Single Tone Trigger Implementation for Seamless and Automated Broadcast to Ad Insertion - Dama, Mardiyan; Windasari, Silviana; Adi Affandi Rotib; Frihadi, Ade; Abdurohman, Abdurohman (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Abstract. The advancement of broadcasting technology has driven the demand for reliable and efficient automation systems, particularly in managing the transition from broadcast content to advertisement segments. In this context, the present study proposes the application of the Single Tone Trigger (STT) method as an automatic triggering mechanism to systematically regulate content switching. This method utilizes a single-frequency audio signal embedded within the primary broadcast, which can be detected by the receiving system. The detection of this signal initiates an automatic content transition without requiring intervention from playout operators. A key advantage of this approach lies in its ease of integration with conventional broadcasting systems and its ability to reduce manual involvement that has traditionally been essential in broadcast content management. Through a series of tests, the system demonstrated high signal detection accuracy, low latency, and optimal operational reliability. These findings indicate that the Single Tone Trigger method can significantly enhance workflow efficiency within the broadcasting industry. Overall, this approach presents substantial potential for broad implementation as an automation solution that is not only stable and cost-effective, but also adaptive to the operational demands of modern broadcasting. Keywords: Automatic Transition, Broadcast Automation, Single Tone Trigger (STT).